Analysis Of Zakat Empowerment In The Era Of Pandemy Covid-19 Towards Impossible Material and Spiritual Aspects Mustahik - Nur Kholidah; Miftahur Rahman Hakim (ITB AAS INDONESIA Surakarta, 2021)
The outbreak of the Covid-19 virus has caused the economy of developing countries to slow down, including Indonesia. The sluggish economy contributes to the poverty rate. Zakat has an important role in the economy and can be a source of funds that can improve welfare. This study aims to analyze the impact of the zakat program in alleviating poverty in mustahik households based on material and spiritual aspects. This research method used a descriptive quantitative approach with a sample of 57 mustahik families who received food security action programs. The statistical test and data analysis used were paired data t-test and the CIBEST model. Based on the CIBEST Model, it shows that zakat's assistance improves the welfare of mustahik and reduces the poverty index of the mustahik material. After the assistance of zakat funds, the Number of mustahik households in the welfare household category (quadrant I) has increased by 0.14 percent. Meanwhile, the Number of mustahik households categorized as material poor (quadrant II) decreased by 0.14 percent.